2011
DOI: 10.1007/s11832-010-0305-3
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in outpatient department visits and operative interventions due to bisphosphonates in children with osteogenesis imperfecta

Abstract: IntroductionBisphosphonates are currently the medical treatment most often used in children with osteogenesis imperfecta (OI). The purpose of this retrospective pre–post study was to evaluate the efficacy of treatment with bisphosphonates. We measured the effect by evaluating the number of outpatient department consultations and operative interventions before and after treatment with bisphosphonates in children with OI.Methods and materialsOutpatient department consultation and operative intervention frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…Graaff ve ark. 118 hastada bifosfonat tedavisini uygulamış ve kırık oluşumunu engellemede ve kırık iyileşmesinde bu tedavinin anlamlı katkısının olduğunu göstermişlerdir (4). Takiplerde kırıkların iyileşmesiyle birlikte deformiteler de görülebilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Graaff ve ark. 118 hastada bifosfonat tedavisini uygulamış ve kırık oluşumunu engellemede ve kırık iyileşmesinde bu tedavinin anlamlı katkısının olduğunu göstermişlerdir (4). Takiplerde kırıkların iyileşmesiyle birlikte deformiteler de görülebilmektedir.…”
Section: Discussionunclassified
“…In this paper, the treatment of fractures and deformity correction in patients with osteogenesis imperfecta using locked intramedullary nailing technique is discussed in the light of the literature. Genel tedavi yaklaşımları arasında ilaç tedavisi (bifosfonatlar, büyüme hormonları, analjezikler), alçı uygulamaları, brace uygulamaları yer almaktadır (3,4). Osteopeni ve korteksteki incelme kırıkların tedavisini de zorlaştırmaktadır.…”
Section: Introductionunclassified
“…14 Overall, bisphosphonate treatment is associated with a reduction of the number of outpatient department consultations and operative interventions. 41 The effects of bisphosphonates seem to be amplified by the growth process, but do not appear to vary much with OI type. Even though OI types I, III and IV constitute the large majority of patients studied until now, responses to pamidronate treatment were observed also in OI types V to VII, even though fracture incidence remained relatively high in OI type VI.…”
Section: Effects Of Intravenous Pamidronatementioning
confidence: 99%
“…Improved bone quality with pamidronate treatment allows better stability of rods in the bone, and improved design of rods reduces the rate of mechanical complications [34] and Graff et al [35] shown that bisphosphonates can significantly reduce the number of outpatient department consultations and operative interventions in patients with OI.…”
Section: Tablementioning
confidence: 99%